PERBANDINGAN PENGATURAN MEKANISME ANTI DUMPING ANTARA INDONESIA DAN TIONGKOK: Comparative of Anti Dumping Mechanism Regulations between Indonesia and China - Rezky Agung Wijayanto Thio; Rosdiana Saleh (Reformasi Hukum Trisakti, 2026)
Dumping practices in international trade have the potential to cause unfair competition and harm domestic industries, thus requiring effective regulatory and law enforcement mechanisms. This study aims to analyze the similarities and differences in the regulation of anti-dumping mechanisms between Indonesia and China as fellow members of the World Trade Organization (WTO). The research question raised is what are the similarities and differences in the regulation of anti-dumping mechanisms between Indonesia and China. The research method used is normative legal research with a comparative law approach, which is descriptive and analytical in nature, using secondary data in the form of legislation and scientific literature. The results show that Indonesia and China both refer to the WTO Anti-Dumping Agreement, but differ in their domestic implementation. Indonesia implements a more legalistic, transparent, and proportional mechanism through the separation of institutional functions and the application of the lesser duty rule principle. In contrast, China uses a centralized system with broad authority vested in a single institution and tends to be protectionist. In conclusion, the differences in these mechanisms reflect the character of each country's legal system and national economic policy orientation, even though they are within the same international legal framework